Enhancing Students' Critical Thinking Skills through Inquiry Learning Model at SMA Negeri 9 Makassar - Suparmin Suparmin (Universitas Muhammadiyah Makassar, 2019)
The research included Classroom Action Research (CAR) with the aim of knowing the improvement of critical thinking skills through the inquiry learning model. Classroom Action Research was carried out at the eleventh MIA 5 grade of sixteen state senior high school of Makassar. The research consisted of two cycles. The first cycle consists of two actions and the second cycle also consists of two actions. The procedure carried out in each cycle consists of planning, implementation, observation, and reflection. For getting the data used the observation sheet and the results of test scores in each cycle. The data analysis technique used descriptive analysis and qualitative analysis. The results of the study showed that it increased through the use of the inquiry learning model. The students critical thinking skills in the first cycle increased even though the increase was not too significant than before the implementation of the inquiry learning model. In cycle one , the students were divided into 5 groups and learning using the free inquiry model then proceed to cycle two critical thinking skills increased from cycle one. In cycle two the number of groups was enlarged into 8 groups and in the learning process students were guided to find so Critical thinking of trained students and can be improved.Keywords: Critical Thinking, Inquiry Learning, StudentsPenelitian ini termasuk Penelitian Tindakan Kelas dengan tujuan untuk mengetahui peningkatan keterampilan berpikir kritis melalui model pembelajaran inquiry. Penelitian Tindakan Kelas dilaksanakan di SMA Negeri 16 Makassar kelas XI MIA 5. Penelitian ini terdiri dari dua siklus. Siklus pertama terdiri dari dua tindakan dan siklus kedua juga terdiri dari dua tindakan. Prosedur yang dilaksanakan pada setiap siklus terdiri dari perencanaan, pelaksanaan, observasi, dan refleksi. Untuk mendapatkan data digunakan lembar observasi dan hasil nilai tes pada setiap siklus. Teknik analisis data yang digunakan adalah analisis deskriptif dan analisis kualitatif. Hasil penelitian menunjukkan bahwa meningkat melalui penggunaan model pembelajaran inquiry. Keterampilan berpikir kritis peserta didik pada siklus I meningkat meskipun peningkatannya tidak terlalu signifikan dari sebelum diterapkannya model pembelajaran inquiry. Pada Siklus I peserta didik peserta didik dibagi menjadi 5 kelompok dan pembelajaran menggunakan model inquiry bebas kemudian dilanjutkan ke siklus II keterampilan berpikir kritis meningkat dari siklus I. Pada siklus II jumlah kelompok diperbesar menjadi 8 kelompok dan pada proses pembelajaran peserta didik dibimbing untuk menemukan sehingga keterampilan berpikir kritis peserta didik terlatih dan dapat meningkat.Kata kunci: Berpikir Kritis, Pembelajaran Inkuiry, Peserta Didik